The Other Wes Moore Bookmark - Kansas State University, K-State First (Kansas State University. K-State First., 2015)
Developed for instructors, this guide to "The Other Wes Moore" by Wes Moore includes a timeline of the characters' lives, discussion questions, thematic information, similar titles, and on-campus resources.
Keywords: The Other Wes Moore; Events; Common reading program; Engagement; First-year experience program; Promotional materials; Promotional materials